O haicai de Paulo Leminski: a busca da forma para sua poesia - Moura, Carla Brogliato Cardoso de (2013)
The main goal of this study is to investigate how the poet Paulo Leminski reveals language awareness under the haiku form, and expresses his sensibility thought it. Particularly questions how far his poetry reveals the haiku s intellectual structure. To guide our research on Paulo Leminski s work, we studied different procedures present in the eastern haiku, like the connection with the Zen gesture, the rhythm and the visual presentation of the letters and words, trying to capture them throughout his poetries. All kinds of poems and different structure options were selected for the analysis, so we could point its plurality. By translating different imagistic procedures, Leminski builds up a form for his own Brazilian haiku, presenting us the craft of his poetry